The weakly coupled chiral Schwinger model on a finite lattice - Pinto, Carlos (Trinity College (Dublin, Ireland). School of Physics, 2000)
The primary aim of this work is the development of a perturbative analysis of the phase structure of the lattice Schwinger model. A novel method for implementing this analysis is presented. It is shown analytically that the photon propagators which appear in the solution can be specified without ambiguity, provided special boundary conditions are implemented on the lattice. A detailed numerical study is carried out to confirm this analytical work. The results of the perturbative calculation indicate the absence of a phase transition in the weakly coupled Schwinger model, contrary to the findings, based on numerical studies, of other groups.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin